Perbedaan Tingkat Pemenuhan Kebutuhan Tidur Pada Lansia Sebelum Dan Sesudah Pemberian Teknik Relaksasi Benson Di Panti Sosial Lanjut Usia Pare Kabupaten Kediri Tahun 2012 - Kun Ika Nur Rahayu (coba, 2015)
Elderly is the last phase of everyone’s life cycle, where they got change biologically, pshycologically, and socialy. Commonly, the elderly got disturbance in quality and quantity sleep needed. Sleeping is a basic needed of all human to be functioned well. According to Luce and Segal (2000). There is 22% elderly cases whose wake up earlier (less than 05.00 p.m) for the elderly in 70 th. Beside, there is 30% for the elderly in 70 th whose wake-up at midnight. One of the solution to solve the problem is using Benson Relaxation technique. This technique can solve the sympthom of sleeplessness such as insomnia, pain and anxiety. The purpose of this research is to know the different the fulfil of sleep needed for elderly before and after giving Benson Relaxation technique in Geriatric Clinic “Lanjut Usia” Pare Kediri in 2012. The research design is pre experimental with one group pre and post test design. The population is elderly in 60-74 years old who got sleeplessness but still can communicate well. The sample is 30 person the sample taken used purposive sampling. It used questionnaire instrument to know the sleep needed of elderly. Then the data analyzed using statistic Willcoxon. The result show, the fulfil of sleep needed for elderly before giving Benson technique is 83% while after giving is 77%. Based on statistic test is gotten ρ=0,00 with α = 0,05. So ρ < α, Ho is rejected. It means, there is the deferent of sleep needed level before and after giving Benson Relaxation technique can be used for nurses to solve the problem of sleep for elderly. Keywords : elderly, sleep, Benson Relaxation